Versatile tethering system to control cell-specific targeting of bioengineered extracellular vesicles - Sheryl Bui; Jeanne Lainé; Maud Chevé; Stéphane Vassilopoulos; Gregory Lavieu (Scientific Reports)
Abstract Extracellular Vesicles (EVs) are natural communication vectors involved in many physiological processes. Significant efforts have aimed to harness EVs for therapeutic delivery, with key challenges being control and enhancement of EV-mediated delivery steps. We and others have developed strategies to improve cargo loading and enhance EV content delivery using viral or non-viral fusogens. However, few targeting solutions have been proposed. Here, we present a versatile system for precise EV targeting to specific cell types, enabling quantitative assessment of targeting efficiency via luminescence and fluorescence. EVs are genetically engineered to express a chimeric adapter protein anchored by a glycosylphosphatidylinositol (GPI) anchor. This protein includes a fluorescent/luminescent domain for detection and a streptavidin domain recruit biotinylated antibodies or ligands specific to cell-surface antigens or receptors. We validated this platform with three different combinations of ligand/target cells, demonstrating up to 40-fold increase in EV uptake. This adaptable system promises to provide a comprehensive solution for targeted therapeutic delivery using EV-based vectors.